A 3-year study of the seasonal variability of abundance, biomass and reproductive traits of Oncaea venusta (Copepoda, Oncaeidae) in a subtropical coastal area. (7th September 2021) - de Melo Júnior, Mauro; Miyashita, Leonardo K; Lopes, Rubens M
Abstract: This study reports on the abundance, biomass and reproductive traits of Oncaea venusta, a common pelagic copepod in tropical oceans, in a coastal area influenced by bottom intrusions of the cold and nutrient-rich South Atlantic Central Water (SACW). In addition to O. venusta abundance and biomass, we estimated egg production and weight-specific fecundity rates by applying the egg-ratio method and incubation experiments, at monthly intervals over 3 years (July 2005–June 2008), to understand potential SACW influences on reproductive patterns. Mean abundance and biomass were low, and no differences were detected with and without SACW intrusions. Mean clutch size (±SD) was 65.1 ± 28.9 eggs female −1 and egg production rates averaged 7.6 ± 12.4 and 9.3 ± 5.2 eggs female −1  day −1 (viability >80%), for the egg-ratio method and incubation experiments, respectively, corresponding to a female weight-specific fecundity from 0.03 ± 0.05 to 0.04 ± 0.06 day −1 . Oncaea venusta abundance and biomass were positively correlated with temperature, but no SACW influence on the reproductive rates was recorded. The egg production rate and the female weight-specific fecundity were influenced by the chlorophyll a concentration and the sex ratio. Although egg production and female weight-specific fecundity rates had peak values during intrusion events, no immediate impact on population abundance was observed within the same time interval.